A figurative analysis of Rupi Kaur’s Milk and Honey - Lukman, Nurul Natasha Karima; Ismail, Wardah; Ab Rahman, Doreen Azlina; Badaruddin, Zuraidar; Lin, Nur Maizura (Universiti Teknologi MARA, 2025)
This paper investigates the various forms of figurative language employed in Rupi Kaur’s Milk and Honey and analyses the context in which these literary devices are utilised. The poet Kaur received mixed reactions from critics for her concise and free-form poetry as well as its emotional impact on society. Her controversial writings explore issues on sexual assault and violence, and it was reported that Milk and Honey is one of the most banned books in the U.S. Thus, this paper aimed to highlight the significance of context in increasing the comprehension of a literature text. The data extracted in this research are based on the four sections in Milk and Honey, namely ‘the hurting’, ‘the loving’, ‘the breaking’ and ‘the healing’. A descriptive qualitative method is employed for the study where data was gathered and analysed through observation and library research. Mainly, the frameworks used in this study were developed by the Knickerbocker and Reninger theory and the Halliday theory in classifying the various figurative language in Milk and Honey. The findings show ten types of figurative language, namely metaphor, personification, irony, hyperbole, allusion, dead metaphor, synecdoche, metonymy, simile and paradox used in Rupi Kaur’s Milk and Honey. The most utilised figurative language was a metaphor and the lowest were dead metaphors and allusion. This study offers insights for educators, which may serve as a pedagogical tool to help students gain a deeper understanding of literary works. Future researchers are suggested to discuss other works by Kaur or other rising poets, focusing on other frameworks, and examine how Kaur’s works are effective at empowering women for the benefit of potential readers.